EPIDEMIOLOGY AND ASSOCIATED FACTORS FOR CAPOEIRA-RELATED MUSCULOSKELETAL INJURIES: A CROSS-SECTIONAL STUDY (Movimenta (ISSN 1984-4298), 2022)
AbstractBackground: Capoeira has been described as beneficial in several aspects, but one of the possible consequences of its growing popularity is the increased account of musculoskeletal injuries among practitioners. An understanding of Capoeira-related musculoskeletal injuries can help sports physical therapists and other health professionals implement preventive strategies.Background: Capoeira has been described as beneficial in several aspects, but one of the possible consequences of its growing popularity is the increased account of musculoskeletal injuries among practitioners. An understanding of Capoeira-related musculoskeletal injuries can help sports physical therapists and other health professionals implement preventive strategies. Objectives: To determine the prevalence of Capoeira-related musculoskeletal injuries and to identify possible associated factors. Methods: This was a cross-sectional study with 520 capoeira practitioners. Survey Web links were emailed to capoeira practitioners associated with specialized groups in Brazil. The Survey collected demographic information, training characteristics and history of Capoeira-related musculoskeletal injuries in the past 12 months. The prevalence of Capoeira-related musculoskeletal injuries was analyzed by descriptive statistics and associated factors by logistic regression models. Results: Most capoeira practitioners (n=411, 79.0%) were men, with a mean age of 29.6±7.6 years old and who trained 3 times a week, over 90 minutes per day, for an average of 13 years of practice. The variable that showed association with Capoeira-related musculoskeletal injuries was weekly training frequency (OR=2.26 95%CI 1.38–3.69). Conclusions: The prevalence of injury was 42.9% (n= 223), and the knee was the most affected joint. The training frequency above 3 times per week was associated with Capoeira-related musculoskeletal injuries.